Juvenile Versus Mature Wood: A New Concept, Orthogonal to Corewood Versus Outerwood, with Special Reference to Pinus radiata and P. taeda - Rowland D. Burdon; R. Paul Kibblewhite; John C. F. Walker; Robert A. Megraw; Robert Evans; David J. Cown (Forest Science, 2004)
Wood properties vary within stems of trees according to genera, species, and individuals. Such variation is largely systematic and is very pronounced in many pines, notably Pinus radiata and P. taeda. While gradual transitions predominate, there are practical needs for categorizing wood, in cutting stems to log lengths, followed by sorting and segregation for processing. Even radial segregation of wood is often possible. In such pines, there are strong, widely recognized progressions, in various wood properties, from pith to bark. Based largely on variation in density, the first few rings from the pith are widely termed juvenile wood, which intergrades outward into wood termed mature wood. Alternative terminology used for this radial progression has been from corewood into outerwood. Critical examination shows the juvenile versus mature wood terminology to be inadequate, on two counts: (1) various other wood properties, some of which can be important, show substantial axial variation at equal ring number from the pith; (2) this categorization based solely on radial variation does not fit the well-established botanical concept of maturation. However, this axial variation closely parallels the vertical variation in shoot morphology and the onset of reproduction that reflect maturation. This argues for a two-dimensional characterization of wood properties: juvenility versus maturity for the progression up the stem, and corewood versus outerwood for the radial progression from the pith to bark. FOR. SCI. 50(4):399–415.